Analysis of the Implementation of a Green Supply Chain-Based Quality Management System in Improving Product Marketing at the Tradjumas Batik Center in Depok - Amrulloh Ibnu Kholdun (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the implementation of a Quality Management System (TQM, ISO 9001:2015) based on Green Supply Chain Management (GSCM) in improving product marketing at the Tradjumas Batik Center in Depok. The method used in this study is qualitative descriptive, which allows researchers to describe and understand the meaning of the data found. This study involved in-depth interviews, participatory observation, and the collection of documentation related to the implementation of TQM, ISO 9001:2015, and GSCM at the Tradjumas Batik Center. The results of the study indicate that although the implementation of TQM and ISO 9001:2015 has had a positive impact on improving product quality, there are obstacles related to limitations in human resources, infrastructure, and managerial commitment. In addition, the implementation of GSCM, although still in its early stages, provides significant added value in improving product competitiveness by adopting environmentally friendly practices. Despite challenges in cost management and supply chain management, the implementation of GSCM plays a crucial role in strengthening product marketing in a market increasingly concerned with environmental sustainability. Overall, the implementation of quality management systems based on TQM, ISO 9001:2015, and GSCM at the Tradjumas Batik Center in Depok demonstrates significant potential in enhancing product quality and competitiveness in both domestic and international markets.